Differences in visual-textual platforms, technical-strategic communication & professionalism vs encroachment between Malaysian & American PR practitioners' social media practices. - Chuan, Tek Pheung; Lee, Cheng Ean Catherine *; Lim, Siz Siz (School of Media and Communication, Taylor's University Malaysia, 2020)
Social media platforms and their affordances are found by researchers to affect the public relations (PR) industry and its practitioners’ tasks. Wright and Hinson’s (2015, 2016, 2017) longitudinal studies showed digital media including online social network sites drastically changing the way PR is practised in the United States. This current localised research adapted and modified Wright and Hinson’s quantitative survey instrument to compare Malaysian and American PR professionals’ social media practices. This exploratory study provides comparative insights into the two countries’ PR practitioners’ preference for visual versus textual-based platforms, technical versus strategic perspectives of social media, and professional PR versus encroachment by marketing. The Internet-based survey (N=95; reliability α=0.782) found differences between Malaysian and American PR practitioners in terms of average time spent on social-media based tasks (above—below 50% majority, respectively); types of social-media platforms preferred for PR work— notably Pinterest and Snapchat (Malaysian) versus Twitter and LinkedIn (American); and the department in charge of social media communication— digital/social media and marketing in Malaysia versus communication/PR in the US.